Global Corporate Financing Approaches and Investment Strategy Optimization: A Comparative Study of Emerging and Developed Markets - Basel, Abioye; Lethabo, Lamond; Tessema, Zola (Journal of Management and Informatics, 2025)
The dynamics of corporate financing strategies have become increasingly complex in an era marked by global uncertainty and diverse market structures. While developed markets often benefit from established institutional frameworks and sophisticated capital access, emerging markets face persistent challenges in striking a balance between sustainability, efficiency, and risk management. This study aims to compare corporate financing approaches across emerging and developed economies, focusing on their effectiveness in optimizing investment decisions and supporting long-term growth. Employing a mixed-method approach, the research combines quantitative analysis of financing performance indicators with qualitative case studies on institutional and governance contexts. The results demonstrate that firms in developed markets tend to rely on equity-based financing and shareholder-driven governance structures, which enhance transparency and facilitate portfolio optimization. Conversely, companies in emerging markets often depend more heavily on debt instruments, public-private partnerships, and adaptive strategies shaped by institutional limitations and behavioral investment patterns. A comparative analysis highlights these structural differences, providing insight into how financing decisions reflect both market maturity and contextual constraints. This study concludes that while developed markets achieve efficiency through established governance and diversified financing channels, emerging markets reveal innovation in addressing volatility and resource scarcity. The findings contribute to the discourse on comparative financial management by bridging theoretical frameworks with practical strategies, offering guidance for policymakers, corporate leaders, and investors seeking sustainable investment outcomes.